Measuring mental health in amyotrophic lateral sclerosis (ALS): a comparison of the SF-36 Mental Health Index with the Psychological General Well-Being Index. - Peto, V; Jenkinson, C; Fitzpatrick, R; Swash, M (2001)
OBJECT: The purpose of this study was to compare the performance of the five-item mental health dimension of SF-36 (the Mental Health Index, MHI-5) with that of the 22-item Psychological General Well-Being Index (PGWB) in patients presenting with amyotrophic lateral sclerosis/motor neuron disease, using tests of reliability and validity. DESIGN: A questionnaire-based survey of patients diagnosed with ALS across 15 European countries. SAMPLE: Patients presenting at neurological clinics for treatment of their ALS were asked to join the survey. RESULTS: 1048 patients with ALS have been recruited, of whom 861 (82.2%) have returned baseline questionnaires. There was evidence supporting the internal consistency of both instruments, and for their construct validity in distinguishing between groups, in terms of gender and age. The scores on the two instruments were highly correlated (Spearman rank correlation 0.85). CONCLUSION: Both the MHI-5 and the PGWB showed high levels of construct validity and internal reliability in this patient group. The MHI-5 has comparable psychometric performance to the PGWB, and can be used to measure and compare mental health in defined populations.